Core temperature and heart rate at the upper limit of the prescriptive zone - Thomas E. Bernard; Candi D. Ashley; S. Tony Wolf; W. Larry Kenney (Physiological Reports, 2023)
Abstract The expressed goal of limiting workplace heat stress exposures to a core temperature (Tc) of 38°C traces back to a 1969 World Health Organization Technical Report (WHO Series 412). The actual goal was to limit exposures to the upper limit of the prescriptive zone (ULPZ). To explore the physiological strain at the ULPZ, progressive heat stress protocol data from Penn State University (PSU) and University of South Florida (USF) below and at the ULPZ were used to articulate the relation of Tc and heart rate (HR) to metabolic rate (MR) with consideration of acclimatization state, clothing, exposure condition (PreULPZ vs. ULPZ), and sex. Regression models demonstrated the association of MR and sex with Tc and HR. At the ULPZ, women had systematically higher values of Tc and HR than men at the same MR likely due to higher relative demands. There was no effect for acclimatization state and clothing. As expected for individuals, Tc was practically constant below the ULPZ and HR exhibited increasing values approaching the ULPZ. At 490 W, the high MR cited in the WHO document, the mean Tc for men was near the 38°C limit with systematically lower Tc at lower MRs.